2021
DOI: 10.3390/v13030434
|View full text |Cite
|
Sign up to set email alerts
|

World-Wide Prevalence and Genotype Distribution of Enteroviruses

Abstract: Enteroviruses (EVs) are highly prevalent viruses world-wide, causing a wide range of diseases in both children and adults. Insight in the global prevalence of EVs is important to define their clinical significance and total disease burden, and assists in making therapeutic decisions. While many studies have been conducted to describe epidemiology of EVs in specific (sub)populations and patient cohorts, little effort has been made to aggregate the available evidence. In the current study, we conducted a search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 74 publications
8
63
1
Order By: Relevance
“…4). The lineage-defining role of enterovirus capsid proteins was the principle exception observed, in line with the traditional serotype classification (12).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…4). The lineage-defining role of enterovirus capsid proteins was the principle exception observed, in line with the traditional serotype classification (12).…”
Section: Discussionsupporting
confidence: 63%
“…At sufficiently long evolutionary distances, niches can be defined by immunological differences, which enable a viral subpopulation to overcome immune cross-protection, allowing the same host to be infected by multiple subpopulations largely independent of prior infections. This phenomenon has been demonstrated for enteroviruses with many co-circulating serotypes (12). These immunological niches do not need to be spatially or temporally segregated.…”
Section: Introductionmentioning
confidence: 70%
“…On the other hand, the Enterovirus C preponderance detected in this study might be a true reflection of EV dynamics in the region sampled during the 2020 EV season. Though Enterovirus C presence has been documented in USA [ 10 ], it has been suggested that this species is not as common in temperate climates as they are in the tropics [ 34 , 35 ]. Little attention has, however, been paid to their dynamics in Southwest US which includes desert climates (such as the region sampled in this study) and it seems, according to our findings, that Enterovirus Cs might circulate well in such.…”
Section: Discussionmentioning
confidence: 99%
“…At sufficiently long evolutionary distances, niches can be defined by immunological differences, which enable a viral subpopulation to overcome immune cross-protection, allowing the same host to be infected by multiple subpopulations largely independent of prior infections. This phenomenon has been demonstrated for enteroviruses with many cocirculating serotypes ( 12 ). These immunological niches do not need to be spatially or temporally segregated.…”
mentioning
confidence: 69%